DISEÑO DE UN SISTEMA FOTOVOLTAICO STAND ALONE, PARA EL SUMINISTRO DE ENERGÍA ELÉCTRICA EN LA UNIDAD EDUCATIVA AMÉRICA - ESPINOZA GONZALEZ, ANGYE YAJAIRA (2025)
The present study, titled "Design of a Stand-Alone Photovoltaic System for Power Supply at Unidad Educativa América", aims to implement a renewable energy solution for this institution, with the objective of reducing electricity billing costs and ensuring a stable, grid-independent power supply